The Effect of Performance, Price Perception, Brand Image, and Brand Association on Purchase Decision of Honda CBR150R in Surabaya - Saktiawan, Ponta Dewa; Harsono, Soni (Philippine Social Science Journal, 2021)
In the automotive industry, the consumer purchase decision is the most important aspect of the company’s life cycle because it can affect profitability, especially for Honda CBR 150R. This study aims to analyze the effect of performance, price perception, brand image, and brand association on the purchase decision of Honda CBR 150R in Surabaya. The research design is descriptive-correlational. Data were collected by distributing 113 questionnaires to the respondents who met the inclusion criteria. The data were analyzed using multiple regression analysis. This research shows that performance and price perception have a negative effect on purchase decisions, but not significantly. The brand image has a positive effect on the purchase decision, but not significantly. On the other hand, the brand association has a positive and significant effect on a purchase decision. It can be concluded that brand association is the most important aspect in Honda CBR 150R purchase decision.